DAKWAH SEBAGAI AKTIVITAS SEJARAH - Yulianti; Fitriani Aisyah, Fia; Afidah, Ida (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
ِThe history of Islamic da'wah is generally divided into three periods, namely: the classical, medieval and modern periods. These three periods have different characteristics, each with their own advantages and disadvantages. During the Nubuwwah period, it was divided into 2 phases, namely the Mecca and Medina phases. Whereas in the Mecca phase the Prophet's preaching was carried out in secret, the target starting from those closest to him, whereas in the Madinnah phase the Prophet's preaching was carried out openly, the target of his preaching was the elite (figures) of society. After the Prophet Muhammad died, the implementation of da'wah was continued by khulafa ar-râsyidin. During this period, the spread and teaching of Islam, as well as the application of Islamic law in people's lives, was accompanied by the expansion of areas where Islam spread. After that, Islamic preaching was continued by the Daulah government, namely the Umayyah Daulah, Abasiah, Usmaniah, Fathimiyyah, and others. Sejarah dakwah Islam secara umum dibagi kepada tiga periode, yaitu: periode klasik, pertengahan dan modern. Ketiga periode tersebut memiliki karakteristik yang berbeda, memiliki kelebihan dan kekurangan masing-masing. Pada masa nubuwwah terbagi menjadi 2 fase, yaitu fase mekkah dan madinnah. Dimana pada fase mekkah dakwah nabi dilakukan secara sembunyi-sembunyi, sasarannya dimulai dari orang- orang terdekat sedangkan pada fase madinnah dakwah nabi sudah dilakukan secara terang- terangan, sasaran dakwahnya adalah kaum elite (tokoh) masyarakat. Setelah Nabi Muhammad wafat, pelaksanaan dakwah dilanjutkan oleh khulafa ar- râsyidin. Pada masa ini, penyebaran dan pengajaran Islam serta penerapan syariat Islam dalam kehidupan masyarakat, diiringi dengan meluasnya daerah penyebaran Islam. Setelah itu dakwah Islam dilanjutkan oleh pemerintah Daulah, yaitu Daulah Umayyah, Abasiah, Usmaniah, Fathimiyyah, dan lain-lain.